Bioremediation of Oil-Contaminated Soils of the Zhanazhol Deposit from West Kazakhstan by Pseudomonas mendocina H-3 - Yerlan Doszhanov; Aitugan Sabitov; Zulkhair Mansurov; Gulzhan Kaiyrmanova (Applied and Environmental Soil Science)
The culture of Pseudomonas mendocina H-3 was selected as the microorganism for oil destruction, and its effect on oil-contaminated soil from the Zhanazhol deposit in West Kazakhstan was studied. After conducting model laboratory experiments, field experiments were carried out. Six and twelve months after the treatment of the oil-contaminated field with microorganisms, the amount of oil fractions in the soil decreased noticeably, while the content of asphaltenes remained constant. Analyses show that the composition of the oil fraction changes—the concentration of paraffin-naphthenic—polycycloaromatic components decreases, whereas the relative amount of mono- and bicycloaromatic hydrocarbons increases. The results of the efficiency assessment showed that the use of Pseudomonas mendocina H-3 cell suspension in natural conditions leads to a decrease in the content of hydrocarbons in the soil from 55 to 70%. The lower efficiency of bioremediation with cell cultures in field experiments (on average, 61%) compared with laboratory model studies (reduction of oil content to 79%) is apparently associated with climatic conditions.